2015
DOI: 10.1016/j.exer.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

In vivo electroretinographic studies of the role of GABAC receptors in retinal signal processing

Abstract: All three classes of receptors for the inhibitory neurotransmitter GABA (GABAR) are expressed in the retina. This study investigated roles of GABAR, especially GABACR (GABA(A)-ρ), in retinal signaling in vivo by studying effects on the mouse electroretinogram (ERG) of genetic deletion of GABACR versus pharmacological blockade using receptor antagonists. Brief full-field flash ERGs were recorded from anesthetized GABACR−/− mice, and WT C57BL/6 (B6) mice, before and after intravitreal injection of GABACR antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
(95 reference statements)
1
12
0
Order By: Relevance
“…We also found that blocking GABAc receptors increased the amplitude of OPs and delayed the time-to-peak of OPs, which is in agreement with previous reports in both rats and mice [ 34 36 ]. However, other groups have suggested that GABAc receptors are minimally involved with OPs [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We also found that blocking GABAc receptors increased the amplitude of OPs and delayed the time-to-peak of OPs, which is in agreement with previous reports in both rats and mice [ 34 36 ]. However, other groups have suggested that GABAc receptors are minimally involved with OPs [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Here, we showed that inhibiting GABAa by intravitreal injection of SR significantly decreased the amplitude of the later OPs, although it also slightly increased the amplitude of the b-wave. In mice, GABAa-blockade by SR causes complete attenuation of OPs, except for an OP1-like wavelet [ 34 ], and it has been reported that SR delays the time-to-peak of the b-wave and increases the amplitude of the b-wave [ 55 ]. We suggest that the differences between our b-wave findings and previous reports may result from use of different animal models (rats vs. mice).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If enhanced behavioural contrast sensitivity in pdzk1-KO zebrafish arises from deficits of inhibitory mechanisms, altered bipolar cell responses underlying the b-wave may be modulated by a more generalised change in retinal inhibition. In rodents, antagonist blockage or genetic knockout of the GABAc receptor, a key inhibitory receptor on bipolar cells, leads to a reduced ERG b-wave but increased spontaneous and light-evoked activity in retinal ganglion cells[39][40][41]. How PDZK1 might be involved in the crosstalk between bipolar, amacrine and ganglion cells remains to be investigated.While the observed b-wave deficit points to bipolar or third-order retinal dysfunction, there could be other potential causes.…”
mentioning
confidence: 99%